Produção orgânica e sua influência na paisagem: estudo de caso - Garcia, Nêmorah Bueno Urruzóla (2017)
It is known that since man began to live in society, there was an increase in the use of the environment as a provider of resources for the maintenance of life, thus making the system unsustainable. The great influence that the anthropic action has on the environments, with different forms of occupation and use of the territory directly interfere in the landscape, decharacterizing it with excessive exploitation of its natural resources and consequently loss of biodiversity. It is necessary that there is a change in the way of planning the use of agroecosystems, so it is not a limiting factor for rural development, but on the contrary, guarantee and preservation of quality of natural resources for the future. The relationship among landscape, vegetation and water, is directly associated with the survival of humanity. The objective of this study was to evaluate the influence on soil quality of two crops with two different types of management systems, organic and conventional, and in the local landscape considering the perception (affective) of the landscape by the agroecological farmer. The indicators of soil quality were based on chemical and physical characterization of layers of 0-10 cm, 10-20 cm and 20-40 cm and microbiological analysis of the layer of 0-10 cm. The different types of soil management influenced the soil quality indicators studied. The plantation soil with organic system has chemical, physical and microbiological disadvantages in relation to planation soil in conventional system, however, considering the landscape of organic production system, without application of pesticides and with greater agrobiodiversity, it is validated the use of this system of organic production. The agroecologial farmer demonstrates sense of attachment and satisfaction in relation to land, the landscape and the territory. Knowing the importance and va lue that the property has for him and his descendants, he keeps trying to manage it to let it preserved for future generations.